Antithrombotic components of Malus halliana Koehne flowers. (September 2018) - Cui, Lili; Xing, Meimei; Xu, Lanting; Wang, Junya; Zhang, Xiaofeng; Ma, Changyang; Kang, Wenyi
Abstract: Flowers of Malus halliana ( M. halliana ) Koehne have been used as a Chinese traditional medicine to treat metrorrhagia and in our study, its chemical composition and anticoagulant effect were investigated. Five compounds were isolated and identified from M. halliana flowers, including limocitrin-3-O-glucoside (1 ), baohuoside Ⅱ (2 ), kaempferol-3-O-α-L-furan arabinoside (3 ), phloretin-4′-O-glycosidase (4 ) and afzeloside (5 ). Compound1–3 were isolated for the first time from this genus. The anticoagulant effect of the compounds and extracts of M. halliana flowers were evaluated by APTT, PT, TT and FIB on plasma of rabbit in vitro . The results indicated that several fractions of M. halliana flowers and compounds2 –5 exhibited anticoagulant activity in vitro. Subsequently, afzeloside (5 ), the abundant component in M. halliana flowers, was investigated further for its antithrombotic effect in vivo and its antithrombotic mechanisms were evaluated on rats acute blood-stasis model. The antithrombotic effect was evaluated by WBV, PV, HCT, ESR, APTT, PT, TT, FIB, 6-keto-PGF1α, TXB2, ET-1 and eNOS in vivo . Afzeloside demonstrated inhibitory effect of thrombus formation, and its underlying antithrombotic mechanism was found to be related to the regulation of vascular endothelium active substance, activating blood flow and anticoagulant effect. Hence, we postulate that flavonoids may be the active ingredients of the plant. Graphical abstract: Highlights: Chemical composition of Malus halliana Koehne flowers were investigated for the first time in this paper. Anticoagulant effect of Malus halliana Koehne flowers in vitro were studied for the first time in this paper. Antithrombotic mechanisms of afzeloside in vivo were studied for the first time in this paper.